Bioactivity Studies of Solanum ferox L. Against Tribolium castaneum (Herbst) Adults (Journal of Life and Earth Science, 2014)
Dose-mortality and repellent activity tests of the chloroform extracts of fruit, leaf, root and stem of Solanum ferox L. against the red flour beetle Tribolium castaneum (Herbst) adults have been done. The fruit, leaf and stem extracts offered promising toxicity to the beetles within 30 min. of exposure. The LD50 values for 30 min., 12, 24, 36 and 48h of exposures were 0.440, 0.247, 0.211, 0.207 and 0.164mg cm-2 respectively for the fruit extract; 2.394, 1.712, 1.540, 1.239 and 0.993mg cm-2 respectively for the leaf extract; and 4.918, 0.871, 0.546, 0.472 and 0.522mg cm-2 respectively for the stem extract. However, the root extract did not offer any mortality for 30 min. and 12h of exposure; and thus the LD50 values for 24, 36 and 48h of exposure were 6.667, 5.086 and 3.357mg cm-2 respectively. While the dose-mortality activity can be arranged in the order of fruit> leaf> stem> root extracts. The fruit and stem extracts showed repellent activity against T. castaneum adults at P